Measuring employment and unemployment - Eliana Viviano; Andrea Brandolini (IZA World of Labor, 2018)
Measuring employment and unemployment is essential for economic policy. Internationally agreed measures (e.g. headcount employment and unemployment rates based on standard definitions) enhance comparability across time and space, but changes in real labor markets and policy agendas challenge these traditional conventions. Boundaries between different labor market states are blurred, complicating identification. Individual experiences in each state may vary considerably, highlighting the importance of how each employed or unemployed person is weighted in statistical indices.
Keywords: J21; J31; J64; J82; J23; 330; employment; unemployment; inactivity; work intensity; search intensity